1998
DOI: 10.1002/(sici)1521-4141(199801)28:01<164::aid-immu164>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte chemotactic protein 2 acts via both IL- 8 receptors, CXCR1 and CXCR2

Abstract: Interleukin-8 (IL-8) acts on human neutrophils via two receptors, CXCR1 and CXCR2. It shares CXCR2 with all neutrophil-activating chemokines, which like IL-8 have a conserved Glu-Leu-Arg (ELR) N-terminal motif, but is generally considered to be the only relevant agonist for CXCR1. IL-8 has a basic residue at the sixth position after the second cysteine, which was suggested to contribute to CXCR1 specificity. Among the other ELR chemokines, only granulocyte chemotactic protein 2 (GCP-2) has such a basic determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 23 publications
2
88
0
2
Order By: Relevance
“…Like other members of the chemokine receptor family, CXCR2 can stimulate cell migration in response to gradient concentrations of ligand (Loetscher et al, 1994;Wolf et al, 1998;Wuyts et al, 1998;Feniger-Barish et al, 2000). Previous studies have demonstrated that vesicle recycling is necessary for cell migration (Bretscher 1992;Hopkins et al, 1994).…”
Section: Role Of Receptor Recycling In Cxcr2 and Cxcr4-mediated Chemomentioning
confidence: 99%
“…Like other members of the chemokine receptor family, CXCR2 can stimulate cell migration in response to gradient concentrations of ligand (Loetscher et al, 1994;Wolf et al, 1998;Wuyts et al, 1998;Feniger-Barish et al, 2000). Previous studies have demonstrated that vesicle recycling is necessary for cell migration (Bretscher 1992;Hopkins et al, 1994).…”
Section: Role Of Receptor Recycling In Cxcr2 and Cxcr4-mediated Chemomentioning
confidence: 99%
“…Furthermore, the secreted IL-8 levels were in most cases at least 10 times higher compared with those of GCP-2. IL-8 and GCP-2 are the only ELR ϩ CXC chemokines that chemoattract and activate neutrophils by binding to both CXCR1 and CXCR2, whereas the other ELR ϩ CXC chemokines only signal through CXCR2 (Wolf et al, 1998;Wuyts et al, 1998a). However, IL-8 is more potent than GCP-2 at activating neutrophils (Proost et al, 1993).…”
Section: Regulation Of Gcp-2 In Connective Tissuementioning
confidence: 99%
“…Human IL-8 and GCP-2 are the only ELR ϩ CXC chemokines that recognize both the receptors CXCR1 and CXCR2 (Murphy et al, 2000;Wolf et al, 1998;Wuyts et al, 1998a). IL-8 is the first identified member of this chemokine subgroup and is the most potent neutrophil chemotactic and activating protein (Wuyts et al, 1998b).…”
mentioning
confidence: 99%
“…The chemokine receptor CXCR2 promiscuously binds all known angiogenic ELR ϩ CXC chemokines, including IL-8, the growth-regulated oncogene family members (GRO-␣, -␤, and -␥), NAP-2, GCP-2, and ENA-78 with high affinity (29,30). In contrast, CXCR1 specifically binds only IL-8 and GCP-2 (30,31). Both CXCR1 and CXCR2 are members of the seven-transmembrane domain rhodopsin-like G protein-coupled receptor superfamily and share 78% amino acid sequence homology (32).…”
mentioning
confidence: 99%